RANCANG BANGUN SOLAR TRACKER DENGAN PENGUKURAN ARUS DAN TEGANGAN SECARA DIGITAL BERBASIS MIKROKONTROLER - Saputra, Erwin Ardias; Fauzi, Rizana; Sollu, Tan Suryani; Demmassewa, Jurnianto (Foristek, 2023)
The design of a solar tracker with digital current and voltage measurements based on a microcontroller is a system that can follow the direction of the sun automatically based on the LDR sensor. The working principle of this tool is to direct the solar panels to follow the direction of the sun automatically and the current and voltage can be monitored digitally based on a data logger. The result of this design is that the solar tracker is programmed using Arduino Uno as the control center, LDR sensor for detecting sunlight as a determinant of the slope of the solar panel to the sun. To drive it, it uses two (2) power window motors which are controlled using the BTS7960 motor driver, and uses the INA219 sensor to measure the current and voltage. The output current and voltage of the solar panel is displayed on the LCD (Liquid Crystal Display) and can be monitored using the PLX-daq data logger.